Cytokine-Defined B Cell Responses as Therapeutic Targets in Multiple Sclerosis - Li, Rui; Rezk, Ayman; Healy, Luke M.; Muirhead, Gillian; Prat, Alexandre; Gommerman, Jennifer L.; Bar-Or, Amit, MSSRF Canadian B cells in MS Team (Frontiers in Immunology, 2016)
Important antibody-independent pathogenic roles of B cells are emerging in autoimmune diseases including multiple sclerosis (MS). The contrasting results of different treatments targeting B cells in patients (in spite of predictions of therapeutic benefits from animal models) call for a better understanding of the multiple roles that distinct human B cell responses likely play in MS. In recent years, both murine and human B cells have been identified with distinct functional properties related to their expression of particular cytokines. These have included regulatory (Breg) B cells (secreting IL-10 or IL-35), and pro-inflammatory B cells (secreting TNFɑ, LT, IL-6 and GM-CSF). Better understanding of human cytokine-defined B cell responses is necessary in both health and diseases such as MS. Investigation of their surface phenotype, distinct functions and the mechanisms of regulation (both cell-intrinsic and -extrinsic) may help develop effective treatments that are more selective and safe. In this review, we focus on mechanisms by which cytokine-defined B cells contribute to the peripheral immune cascades that are thought to underlie MS relapses, and the impact of B cell-directed therapies on these mechanisms.